Efficacy and safety of atacicept for prevention of flares in patients with moderate-to-severe systemic lupus erythematosus (SLE): 52-week data (APRIL-SLE randomised trial). Issue 11 (20th June 2014) - Isenberg, David; Gordon, Caroline; Licu, Daiana; Copt, Samuel; Rossi, Claudia Pena; Wofsy, David
Abstract : Objectives: Despite advances in systemic lupus erythematosus (SLE) treatment, many patients suffer from the disease and side effects. Atacicept is a fusion protein that blocks B-lymphocyte stimulator and a proliferation-inducing ligand, which are increased in patients with SLE. Methods: In this double-blind, placebo-controlled study, patients with moderate-to-severe SLE were randomised to atacicept 75 mg or atacicept 150 mg administered subcutaneously, or placebo twice-weekly for 4 weeks, then weekly for 48 weeks. Primary and secondary efficacy measures were the proportion of patients experiencing at least one flare of British Isles Lupus Assessment Group A or B, and time to first flare, respectively. Results: Enrolment in the atacicept 150 mg arm was discontinued prematurely due to two deaths. In the intention-to-treat population (n=461), there was no difference in flare rates or time to first flare between atacicept 75 mg and placebo. Analysis of patients treated with atacicept 150 mg suggested beneficial effect versus placebo in flare rates (OR: 0.48, p=0.002) and time to first flare (HR: 0.56, p=0.009). Both atacicept doses were associated with reductions in total Ig levels and anti-dsDNA antibodies, and increases in C3 and C4 levels. Most treatment-emergent adverse events were mild or moderate. Conclusions: There was no difference between atacicept 75 mg and placebo for flare rate or time to first flare. Analysis of atacicept 150 mg suggested benefit. Trial registration number: EudraCT: 2007-003698-13; NCT00624338 .